ANALISIS PERTUMBUHAN EKONOMI INDONESIA TAHUN 2000:1 â 2013:4 MODEL IS-MP-IA - , ANISAH NURUL MAWADDAH; , Dr. Suratno, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to analyze the effect of endogenous variables and exogenous variables to Indonesian output in the short term and long term. The data used in study are data in year 2000 quarter 1 to year 2013 quarter 4. This study finds that a higher on CPI, exchange rate, world output and a lower on ratio government spending to GDP, federal funds rate, would help increase the Indonesian real GDP. Federal funds rate as exogenous variable has the effect in the short-term and long-term. The other exogenous variable, world output, has no effect in the short-term and the long term to the Indonesian Real GDP.